Photoinduced Photocatalyst-Free Cascade Cyclization of Alkynes with Sodium Sulfinates for the Synthesis of Benzothiophenes and Thioflavones - Dong, Hongqiang; Chen, Chunli; Zhao, Jinlei; Ji, Yigang; Yang, Wenchao (Molecules (Basel, Switzerland), 2023)
The subject of this investigation is a new method for the construction of sulfonylated heterocycles which overcomes the limitations of classical approaches using a cheap feedstock sulfonylating agent, especially under photocatalyst- and metal-free conditions.